2018
DOI: 10.1002/jobm.201700462
|View full text |Cite
|
Sign up to set email alerts
|

Annotation of gut bacterial taxonomic and functional diversity in Spodoptera litura and Spilosoma obliqua

Abstract: The insect gut has been the house of many taxonomically and physiologically diverse groups of microbial colonizers as symbionts and commensals, which are evolving to support the physiological requirement of insects. Lepidoptera is one of the important family of class hexapoda, comprising agriculture insect pest Spodoptera litura and Spilosoma obliqua. Information on gut microbiota and their functional role in these insects was meager to elucidate the wide-ranging survivalist mechanisms. In this context, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…These results are in accordance with a recent study that used high‐throughput sequencing of 16S rDNA to analyse the gut microbiota of late‐instar field‐captured H. armigera larvae, where Actinobacteria was the dominant phylum followed by Proteobacteria and Firmicutes (Ranjith et al, ). Moreover, in another study that also used next‐generation sequencing of 16S rDNA, a very high proportion of the S. litura larval gut microbiota corresponded to uncultured Bacteria (Bapatla et al, ). Nevertheless, two other studies that analysed the gut microbiota in S. littoralis found that, in late‐instar larvae, both taxonomically and metabolically (although in different proportions), Firmicutes was by far the most abundant phylum, followed by Proteobacteria, and that Enterococcus (Firmicutes) was the most active genus, and to a lesser degree, Clostridium (Firmicutes) and Pantoea (Proteobacteria; Chen et al, ; Shao et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are in accordance with a recent study that used high‐throughput sequencing of 16S rDNA to analyse the gut microbiota of late‐instar field‐captured H. armigera larvae, where Actinobacteria was the dominant phylum followed by Proteobacteria and Firmicutes (Ranjith et al, ). Moreover, in another study that also used next‐generation sequencing of 16S rDNA, a very high proportion of the S. litura larval gut microbiota corresponded to uncultured Bacteria (Bapatla et al, ). Nevertheless, two other studies that analysed the gut microbiota in S. littoralis found that, in late‐instar larvae, both taxonomically and metabolically (although in different proportions), Firmicutes was by far the most abundant phylum, followed by Proteobacteria, and that Enterococcus (Firmicutes) was the most active genus, and to a lesser degree, Clostridium (Firmicutes) and Pantoea (Proteobacteria; Chen et al, ; Shao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One of these studies showed that bacteria isolated from the P. xylostella gut had the ability to fix nitrogen in vitro (Indiragandhi et al, ). The other study analysed the gut metagenome of S. litura and Spilosoma obliqua Walker (Lepidoptera: Erebidae) through high‐throughput sequencing of 16S rDNA and indirectly inferred a high abundance of bacterial ammonia oxidizers by taxonomic to phenotypic mapping of the datasets (Bapatla et al, ; Table S6). Our study strongly suggests that Bacteria and Archaea were expressing transcripts associated with nitrogen utilization in the larval guts of field‐captured S. frugiperda , likely due to their great voracity and ensuing need to metabolize the ingested nitrogen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have begun to explore gut microbial diversity and function of S. litura . Bapatla et al (2018) used the V3 region of 16S rRNA to amplify the gut bacteria in S. litura and then sequenced them on the Illumina MiSeq platform, revealing that the gut bacteria of S. litura were composed of 27% Proteobacteria and 14% Chlorobi. Proteobacteria was the most abundant phylum in the S. litura gut, however, 34% of unclassified bacteria in the V3 region were relatively short and difficult to annotate ( Bapatla et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%